Features of dissomnia and cognitive impairments in chronic cerebral ischemia due to diabetes mellitus type 2 - Yu. I. Kotsenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Currently, diabetes mellitus occupies a leading position in terms of prevalence, disability, mortality and it is a medical and social problem. Microvascular and macrovascular diabetic complications negatively affect the quality and duration of sleep with detrimental effects on metabolism and weight regulation. The cognitive sphere is more impaired in type 2 diabetes mellitus in the form of a decrease in the speed of reaction to external stimuli and the ability to concentrate for a long time, so thinking becomes slower, and clinically significant cognitive impairments leads to work and social maladaptation and a decrease in adequate glycemic control. Aim of the study: to study the nature of diagnosed cognitive impairments and variants of dissomnias in chronic cerebral ischemia and to evaluate the features of identified dissomnias in the development of early dementia in type 2 diabetes mellitus. Object and methods. During the period from 2017 to 2023, 207 patients with chronic cerebral ischemia and neurological deficits of varying severity were examined. All patients underwent a comprehensive clinical and neurological examination using specialized scales to study the cognitive sphere and sleep level, laboratory and instrumental methods of examination. The study applied non-inclusion, inclusion and exclusion criteria and selected 147 patients with chronic cerebral ischemia and type 2 diabetes mellitus. The data has been processed statistically. Results. Cognitive impairments (95,1 ± 2,4%) and dyssomnia (88,9 ± 3,5%) develop in patients with type 2 diabetes mellitus with chronic cerebral ischemia, and their combination is significant (p < 0,05) prevailed (82,7 ± 4,2%) with dysmetabolic signs. At the same time, moderate (43,2 ± 5,5%) and severe (34,6 ± 5,3%) cognitive disorders with moderate dyssomnia (63,0 ± 5,4%) and increased sleepiness (64,2 ± 5,3%) with episodes of obstructive sleep apnea (16,0 ± 4,1%) and narcolepsy (6,2 ± 2,7%) compared with patients without type 2 diabetes mellitus (p < 0,05). Conclusions. The presence of type 2 diabetes mellitus increased the risk of developing dyssomnia and cognitive disorders, and the identification of dyssomnia led to an increased chance of a deterioration in the intellectual-mnestic level to the degree of moderate and severe impairments. Neuropsychological testing in combination with dyssomnia questionnaires and quantitative assessment of the severity of cognitive dysfunction is absolutely necessary.